2020
DOI: 10.1177/0739986320910165
|View full text |Cite
|
Sign up to set email alerts
|

Latinx College Students: How Schemas and Attachments Impact Depression and Relationship Satisfaction

Abstract: Latinx college students face challenges regarding depression. The relationships between early maladaptive schemas (EMS) and attachment style on depression and relationship satisfaction were investigated among 236 Latinx college student participants. The Young Schema Questionnaire–Short Form (YSQ-S3) total score was utilized to identify overall schema. Significant correlations were found. Overall schema, attachment anxiety, attachment avoidance, and depression were all positively correlated, while attachment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Rarely, however, have the links between attachment and psychopathology been examined in all‐Latinx samples, with the findings in one study showing associations between anxiety, but not avoidance, and greater depression in Latinx youth (Ulloa et al, 2014), while another found secure attachment to be significantly negatively associated with all forms of psychopathology in a sample of immigrant Latinx youth from Central America (Venta et al, 2019). Additionally, a study of Latinx college students found that both attachment anxiety and attachment avoidance were positively associated with depressive symptoms (Rodriguez et al, 2020). With respect to the link between attachment and anxiety symptoms, while little work has examined these associations among Latinx youth, a meta‐analysis of 46 studies conducted between the years of 1984–2010, which included 8907 children, revealed an overall effect size of r = .30 (Colonnesi et al, 2011).…”
Section: Factors Predicting Mental Health In Latinx Familiesmentioning
confidence: 99%
“…Rarely, however, have the links between attachment and psychopathology been examined in all‐Latinx samples, with the findings in one study showing associations between anxiety, but not avoidance, and greater depression in Latinx youth (Ulloa et al, 2014), while another found secure attachment to be significantly negatively associated with all forms of psychopathology in a sample of immigrant Latinx youth from Central America (Venta et al, 2019). Additionally, a study of Latinx college students found that both attachment anxiety and attachment avoidance were positively associated with depressive symptoms (Rodriguez et al, 2020). With respect to the link between attachment and anxiety symptoms, while little work has examined these associations among Latinx youth, a meta‐analysis of 46 studies conducted between the years of 1984–2010, which included 8907 children, revealed an overall effect size of r = .30 (Colonnesi et al, 2011).…”
Section: Factors Predicting Mental Health In Latinx Familiesmentioning
confidence: 99%
“…We purpose that early maladaptive schema factors predict depressiveness (42,43,44,45,46) and that pain is the end state(46).…”
Section: Objectivementioning
confidence: 99%
“…For example, family cohesion has been associated with problem-solving skills and positive self-concept among young adults (Leidy et al, 2010) and with better parenting behaviors (Romero & Ruiz, 2007). Specifically, research done with Latinx college students shows associations between parental attachment styles and developmental schemas and relationship satisfaction (Rodriguez et al, 2020), indicating that family experiences have an impact on relationship satisfaction. Although our measure of familism focuses on social support and the importance of relationships, these previous findings highlight the central role family plays in impacting relationship outcomes.…”
Section: Familism As a Protective Factormentioning
confidence: 99%